A High-frequency Study on Uncovered Interest Parity between the Asean-5 Vis-À-Vis the U.S. - Lim, Tze Jian (2010)
This study follows in the footsteps of Chaboud and Wright (2005) who are among the very few to my knowledge to use high-frequency intraday data in their UIP study. I test the UIP using 1-minute spot exchange rate data and daily interest rates (interbank offer rates) of the ASEAN-5 member countries – Indonesia, Malaysia, Philippines, Singapore, Thailand. I run regressions on the approximate form of UIP using a simple econometric technique, OLS. I run these regressions using different time-interval (i.e. intervals of 1-, 2-, 3-, 4-, 5-minutes) and date-interval (December 2009-December 2009, December 2009-January 2009, December 2010-February 2010 etc.) combinations. I obtain results which show both positive and negative coefficients, all of which are very close to zero, some of which are significantly different from zero. This lack of support for UIP may be attributable to the sample period chosen, December 2009-June 2010, which is in the aftermath of the U.S. subprime crisis.